Organes du corps et dispositifs de la forge chez les Moose du Burkina Faso - Lidia Calderoli (Ateliers d'Anthropologie)
Moose smiths employ tools normally used for iron work in order to perform therapeutic rites. Their work enables them to develop a specific imaginative world concerning the body, and their rituals are based on metaphorical techniques.Moose smiths compare the body’s organs not only to tools, but also to wrought iron. An example of these parallels is offered by the therapeutic rite that aims to treat an illness affecting the last section of the intestine (particularly an anal or rectal prolapse). The forge bellows that is used in that case is essential for analogies that are drawn between the body and the forge; and the bellows nozzle is used to treat that illness, which is attributed to having infringed the forge’s domain through a certain type of theft. A local description of causes, symptoms and treatment brings out a network of analogies that link the human body to the bellows nozzle and to iron work.These analogies fit coherently into an ideology explained by the smiths, concerning their role as tool producers and guarantors of agricultural work. The bellows nozzle and its associated illness therefore become material devices that, through non-arbitrary signs and physical effects, recall the forgotten link between the powers connected with forging and men, and by the same token, the links between smiths and non-smiths. Consequently, the body of the infirm individual reflects a broader social body, his family and his relations with smiths a group. Through the use of forging tools, the treatment rite refers to illness in its broadest social sense.